The Direct Impact of the Project-based Learning ((PjBL) Model on the Physical Motor Development of Early Childhood - Ayu Mustika Sari Ayu; Amalia Husna; Yennizar.N (Universitas Pendidikan Ganesha, 2025)
Motor development is an essential aspect of early childhood education because it supports children’s learning readiness as well as their overall physical, cognitive, and social development. However, in many early childhood learning practices, motor stimulation has not been optimally implemented, as instructional activities tend to focus more on academic achievement. This condition highlights the need for learning models that are capable of integrating learning activities with active motor stimulation. This study aims to analyze the effect of the Project-Based Learning (PjBL) model on early childhood motor development. The study employed a quantitative approach with a quasi-experimental design, involving children aged 5–6 years who were divided into an experimental group and a control group. Data were collected using a motor development checklist instrument that included indicators of both fine and gross motor skills. Data analysis was conducted through statistical prerequisite tests and an independent sample t-test to examine the effect of the implemented learning model. The results indicate that children’s motor development in the group that participated in learning using the Project-Based Learning model was higher than that of children who participated in conventional learning. Improvements in motor skills were reflected in children’s involvement in various project activities that required movement coordination and the active use of tools. These findings suggest that the Project-Based Learning model is effective in stimulating early childhood motor development and can serve as an alternative instructional strategy to support holistic child development.